2011
DOI: 10.3168/jds.2011-4348
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric differential cell counts in milk for the evaluation of inflammatory reactions in clinically healthy and subclinically infected bovine mammary glands

Abstract: Somatic cell counts (SCC) are generally used as an indicator of udder health. In Germany, a cutoff value of 100,000 cells/mL is currently used to differentiate between healthy and diseased mammary glands. In addition to SCC, differential cell counts (DCC) can be applied for a more detailed evaluation of the udder health status. The aim of this study was to differentiate immune cells in milk of udder quarters classified as healthy based on SCC values of <100,000 cells/mL. Twenty cows were selected and 65 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 43 publications
9
97
0
3
Order By: Relevance
“…aureus mono-infection revealed lower SCC mean values in Mediterranean buffaloes (4.82 ± 0.23 Log 10 cells/mL) as compared with those detected for cows (5.97 ± 0.49 Log 10 cells/mL; Graber et al, 2009). Interactions among infection, inflammatory processes, and immune responses in individual udder quarters are still controversially discussed in dairy cows (Schwarz et al, 2011), whereas in dairy buffalo no complete studies are present to explain the relationship. Different leukocyte behavior during the initial phase of the inflammation and stronger pressure from udder pathogenic microorganisms of the environment or stressful events (i.e., kicking during premilking preparation of the udder or during taking the quarter foremilk samples) might have triggered the elevation of the SCC and may explain the difference observed between the 2 species.…”
Section: Discussionmentioning
confidence: 93%
“…aureus mono-infection revealed lower SCC mean values in Mediterranean buffaloes (4.82 ± 0.23 Log 10 cells/mL) as compared with those detected for cows (5.97 ± 0.49 Log 10 cells/mL; Graber et al, 2009). Interactions among infection, inflammatory processes, and immune responses in individual udder quarters are still controversially discussed in dairy cows (Schwarz et al, 2011), whereas in dairy buffalo no complete studies are present to explain the relationship. Different leukocyte behavior during the initial phase of the inflammation and stronger pressure from udder pathogenic microorganisms of the environment or stressful events (i.e., kicking during premilking preparation of the udder or during taking the quarter foremilk samples) might have triggered the elevation of the SCC and may explain the difference observed between the 2 species.…”
Section: Discussionmentioning
confidence: 93%
“…Na glândula mamaria sadia, não há um consenso na literatura, sobre a população leucocitária predominante. Por exemplo, Rivas et al (2001), Dosogne et al (2003) e Schwarz et al (2011) consideram os linfócitos, a população predominante na glândula mamária sadia, porém não utilizaram anticorpos monoclonais específicos para identificar as distintas populações leucocitárias. Refutando essa afirmação, Leitner et al (2000) e Leitner et al (2003) acreditam que células epiteliais são as que predominam.…”
Section: Discussionunclassified
“…Trabalhos empregando a citometria de fluxo (Rivas et al 2001, Koess & Hamann 2008, Schwarz et al 2011, Pilla et al 2013, Blagitz et al 2015, citocentrifugação (Dulin et al 1982, Mira et al 2013) e contagem microscópica direta por esfregaços (Dosogne et al 2003, Pilla et al 2013) já foram realizados. Portanto, o trabalho em questão apresenta suma importância para a comunidade científica uma vez que até o momento, até onde se sabe, não há relatos de trabalhos que avaliem as três técnicas de contagem de células somáticas e sua respectiva relação com o diagnóstico microbiológico.…”
Section: Introductionunclassified
“…The magnitude of the difference, as well as the significantly higher total neutrophils, total macrophages, total lymphocytes, and total phagocytes was consistent with expectations, similar to other studies (PILLAI et al, 2001;DOSOGNE et al, 2003; SCHWARZ et al, 2011a,b;PILLA et al, 2012;PILLA et al, 2013). SCHWARZ et al (2011b) showed that PMNL in milk samples with SCC values < 6.25×10 3 cells/mL were rare (mean proportion = 15%). PILLAI et al (2001) The difference in TLC was striking when quarters infected by any pathogen were compared to healthy quarters, as was the difference in neutrophils%, macrophages% and Log10 N /L.…”
supporting
confidence: 79%
“…The changes in cell ratio have been used for the identification of inflammatory processes in cows with low SCC, with the potential to differentiate milk from healthy quarters from those with early or late inflammation (PILLA et al, 2012). The MLD patterns of 6 out of 41 quarter milk samples with SCC values from ≥9,000 to ≤46,000 cells/mL were described by SCHWARZ et al (2011b) and their results revealed early inflammatory reactions based on the predominance of polymorphonuclear neutrophils (PMNL) (56-75%).The MLD has been tested as an option to identify cows affected by any inflammatory process of the mammary gland, with the best results being reported by using logarithmic 38 PMNL:lymphocyte ratio as the variable (PILLA et al, 2012). However, there is still little knowledge about the MLD and its application under field conditions.…”
mentioning
confidence: 99%